2008
DOI: 10.1111/j.1582-4934.2008.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment alters dentate granule cell morphology in oldest‐old rat

Abstract: IntroductionThe process of aging is usually followed by cognitive decline that is characterized by impairments in a variety of tests for spatial memory [1][2][3][4][5][6]. It is suggested that the anatomical substrate for these impairments is to be found in age-related changes that appear mostly in hippocampal formation [1][2][3][7][8][9][10][11][12][13]. In particular, the dendritic trees of dentate granular cells are the main receptive field for afferent projections in the hippocampus. These cells receive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 118 publications
(214 reference statements)
0
17
0
Order By: Relevance
“…Thus, EE rehabilitationinduced benefits after experimental TBI during development differentially arise as a function of timing postinjury. 102 Further, the benefits of EE are not limited to young subjects because several non-TBI studies have shown that rats up to 24 months of age show an EE-induced attenuation of age-related dendritic regression and synaptic loss, 103 a reduction in spatial memory decline, 104 and increased cognitive function in complex blind-alley maze tasks. 105 EE also confers benefits in aged rats after middle cerebral artery electrocoagulation, as evidenced by improved rate and extent of neurobehavioral recovery, which correlated with smaller infarcts and a reduction in the number of proliferating astrocytes.…”
Section: The Benefits Of Environmental Enrichment Extend Beyond Adultmentioning
confidence: 99%
“…Thus, EE rehabilitationinduced benefits after experimental TBI during development differentially arise as a function of timing postinjury. 102 Further, the benefits of EE are not limited to young subjects because several non-TBI studies have shown that rats up to 24 months of age show an EE-induced attenuation of age-related dendritic regression and synaptic loss, 103 a reduction in spatial memory decline, 104 and increased cognitive function in complex blind-alley maze tasks. 105 EE also confers benefits in aged rats after middle cerebral artery electrocoagulation, as evidenced by improved rate and extent of neurobehavioral recovery, which correlated with smaller infarcts and a reduction in the number of proliferating astrocytes.…”
Section: The Benefits Of Environmental Enrichment Extend Beyond Adultmentioning
confidence: 99%
“…toys), cognitive stimulation, social interactions and physical activity have repeatedly been shown to promote brain plastic changes (e.g. increased cortical thickness, hippocampal dendritic branching and spine density, number of synapses, capillary diameter, neurotrophin levels) and improve learning abilities of rodents at different ages (Diamond et al, 1976, Pham et al, 1999, Ickes et al, 2000, Diamond, 2001, Mohammed et al, 2002, Darmopil et al, 2009, Zhu et al, 2009.…”
Section: Experience Brain and Behaviormentioning
confidence: 99%
“…The complexity differences in EC relative to standard social housing (SH) derives from multiple behavioral variables such as the amount of social interactions between rodents, enhanced exploratory behavior and exposure to novelty (Gelfo et al, 2009). EC is known for its powerful effects on brain plasticity: previous studies have demonstrated that exposure to EC produces increased brain and weight size, increased number of dendritic bifurcations, increased dendritic length, increased spine density and enhanced cell survival (van Praag et al, 2000; Gelfo et al, 2009; Darmopil et al, 2009). The current study tested the hypothesis that exposure to EC following adolescent WR would ameliorate the deficits in long-term survival of newly generated cells in the alcohol-exposed rats demonstrated in our previous study (Helfer et al, 2009), by increasing the long-term survival of newly generated cells relative to animals in SH after WR, and that this survival-promoting effect would be more prominent for the alcohol-exposed rats.…”
Section: Introductionmentioning
confidence: 99%